Greenhouse gas mitigation: Issues for Indian agriculture - Nelson, Gerald C.; Robertson, Richard D.; Msangi, Siwa; Zhu, Tingju; Liao, Xiaoli; Jawajar, Puja (International Food Policy Research Institute, 2009)
By some estimates, agricultural practices account for 20 percent of India’s total greenhouse gas (GSG) emissions; thus, cost-effective reductions in agricultural emissions could significantly lower India’s overall emissions. We explore mitigation options for three agricultural sources of GHGs—methane (CH4) emissions from irrigated rice production, nitrous oxide (N2O) emissions from the use of nitrogenous fertilizers, and the release of carbon dioxide (CO2) from energy sources used to pump groundwater for irrigation. We also examine how changes in land use would affect carbon sequestration. We find great opportunities for cost-effective mitigation of GHGs in Indian agriculture, but caution that our results are based on a variety of data sources, some of which are of poor quality.